Analyze the effects of CNC machining parameters on the surface roughness (Rz) of Anatolian chestnut - Aras, Oruç; Sofuoğlu, Sait Dündar (Bursa Technical University, 2024)
The effect of processing parameters on the surface roughness parameter Rz (mean peak-to-valley height) in CNC machining of Anatolian chestnut (Castenia sativa Mill.) wood species used in the woodworking and furniture industry was investigated. The machining conditions were determined to obtain the lowest Rz value. The experi-ments were carried out at the speeds of 8000, 12000, and 16000 rpm and the feed rates of 1000, 1500, and 2000 mm/min with 3 and 4 machining layers by using two different cutters with a diameter of 8 mm. Rz measurements were made on the obtained surfaces using the needle scanning method according to TS EN ISO 21920-2 (2021). In the measurements perpendicular to the fibers, the lowest Rz values were obtained with cutter type 2 (the cutter of the three cutting edge straight end mill), at 16000 rpm speed, 1000/2000 mm/min feed rate, and four machining layers. In the measurements made parallel to the fibers, the lowest Rz values were obtained at the cutter type 2 (the cutter of the three cutting edge straight end mill), at the speed of 16000 rpm and the feed rate of 1000/2000 mm/min and 4th step-down. A smooth surface (lower Rz value) was obtained with fourth cuts (step down, cut layer) instead of third cuts.

Mobilya ve ağaç işleme sanayiisinde kullanılan yerli ağaç türlerinden Anadolu kestanesi (Castenia sativa Mill.)’nin CNC ile işlenmesinde işleme parametrelerinin Rz yüzey pürüzlülük parametresi üzerine etkisi incelenmiştir. En düşük Rz değerinin elde edilebilmesi için işleme koşulları belirlenmiştir. Denemeler iki farklı kesici kullanılarak (çap=8 mm) 8000, 12000 ve 16000 devir/dakika devir sayılarında ve 1000, 1500 ve 2000 mm/dak ilerleme hızlarında 3 ve 4 olmak üzere farklı iki işleme katman sayısında yapılmıştır. İşleme sonucu meydana gelen yüzeylerin zeminlerinde dokunmalı iğne taramalı yöntem kullanılarak TS 6956 EN ISO 4287’ e göre Rz (ortalama tepe-vadi yüksekliği) tespiti yapılmıştır. Liflere dik yapılan ölçümlerde en düşük Rz değerleri 2 no’lu (3 kesici kenarlı düz parmak freze) kesici tipinde, 16000 dev/dak devir sayısında, 1000/2000 mm/dak ilerleme hızında ve 4 işleme katman sayısında elde edilmiştir. Liflere paralel yapılan ölçümlerde en düşük Rz değerleri 2 no’lu kesici (3 kesici kenarlı düz parmak freze) tipinde, 16000 dev/dak devir sayısında, 1000/2000 mm/dak ilerleme hızında ve 4 işleme katman sayısında elde edilmiştir. 3 kesiş ile alan boşaltma yerine 4 kesiş ile yapılan alan boşaltma da düzgün yüzey (daha düşük Rz değeri) elde edilmiştir.
Anadolu kestanesi (Castenia sativa Mill.)’nin CNC ile işlenmesinde zemin yüzeyde Rz pürüzlülük değerine işleme parametrelerinin etkisi
Keywords: Forest Industry Engineering (Other); Orman Endüstri Mühendisliği (Diğer) [EN] Wood Processing; Ahşap İşleme